2014
DOI: 10.1099/ijs.0.055269-0
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomonas aerophila sp. nov. and Sphingomonas naasensis sp. nov., isolated from air and soil, respectively

Abstract: Two strains, designated 5413J-26T and KIS18-15T, were isolated from the air and forest soil, respectively, in South Korea. Cells of the two strains were Gram-stain-negative, aerobic, polar-flagellated and rod-shaped. According to the phylogenetic tree, strains 5413J-26T and KIS18-15T fell into the cluster of Sphingomonas sensu stricto. Strain 5413J-26T showed the highest sequence similarities with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…S3). However, the polar lipid profile of strain E62-3 T lacked sphingoglycolipid which was similar to Sphingomonas aerophila and Sphingomonas naasensis (Kim et al, 2014). 6.0-9.0 6.0-9.0 5.0-9.0 6.0-11.0 NaCl (%, w/v) tolerance 0.5 3 5 0.5 Kaur et al (2012); b, Chen et al (2013); c, Yasir et al (2010).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…S3). However, the polar lipid profile of strain E62-3 T lacked sphingoglycolipid which was similar to Sphingomonas aerophila and Sphingomonas naasensis (Kim et al, 2014). 6.0-9.0 6.0-9.0 5.0-9.0 6.0-11.0 NaCl (%, w/v) tolerance 0.5 3 5 0.5 Kaur et al (2012); b, Chen et al (2013); c, Yasir et al (2010).…”
mentioning
confidence: 60%
“…The major polyamine homospermidine was found in the genera Sphingomonas and Sphingosinicella, while spermidine was present in the genera Novosphingobium, Sphingobium, and Sphingopyxis Busse et al, 2003;Maruyama et al, 2006). Members of the genus Sphingomonas were isolated from various samples, such as soil, air, water, marine bivalve specimen and a lead-zinc mine (Lee et al, 2001;Romanenko et al, 2007;Lin et al, 2012;Son et al, 2013;Feng et al, 2014;Kim et al, 2014). All strains in the genus are Gram-stain-negative, aerobic, rod-shaped and catalase-positive Chen et al, 2012a;Kaur et al, 2012).…”
mentioning
confidence: 99%
“…16S rRNA gene amplicon sequencing revealed that Sphingomonas was the most frequently detected genus in the air samples. This genus has been found in various environments such as soil, water, clinical specimens, air, and other locations [30][31][32], indicating the opportunity for the bacteria to be released into the air. Pseudomonas and Achromobacter were signi cantly more abundant in air samples from bathrooms and other indoor sites, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…net/ sphingomonas. html), the genus Sphingomonas contains 131 recognized species isolated from various natural sources, such as air, soil [7][8][9], groundwater [10], marine bivalves [11] and freshwater sediments [12]. The present study reports on the taxonomic characterization of a Sphingomonas-like bacterial strain (designated LMO-1 T ) isolated from marine sediment.…”
Section: Sphingomonas Profundi Sp Nov Isolated From Deep-sea Sedimmentioning
confidence: 94%